10 years EU regulation of pediatric medicines – impact on cardiovascular drug formulations. (4th March 2018) - Thabet, Yasmin; Slavkova, Marta; Breitkreutz, Jörg
ABSTRACT: Introduction : Child-appropriate drug formulations are mandatory for an efficient and safe drug therapy in children. Since the implementation of supportive legislations development of novel drug formulations has significantly been enforced despite the fact that children are a heterogeneous group of patients with varying needs according to age, maturation and disease. Areas covered : In this review, recent advances and current strategies are evaluated how to overcome the specific hurdles in pediatric drug development. For cardiovascular diseases as an example, EMA's decisions on pediatric investigation plans (PIPs) have been evaluated. New developments with innovative platform technologies such as mini-tablets and orodispersible preparations have been identified indicating a clear shift from liquid preparations to small-sized solid (multiparticulate) or orodispersible dosage forms. Reasons for this shift of paradigm are discussed. Expert opinion : Innovative platform technologies for solid drug dosage forms such as mini-tablets, orodispersible tablets or film preparations will continue to conquer the pharmaceutical market. Still, there are some major issues to be resolved, e.g. how to ensure quality of the new dosage forms and dose accuracy in flexible dosing, but the governmental incentives will continue to accelerate development of pediatric medicines and will bridge the still existing gaps in the near future.